Sleep health among people with severe mental ill health during the COVID-19 pandemic: Results from a linked UK population cohort study - Heron, Paul N.; Henderson, Lisa M.; Crosland, Suzanne; Gilbody, Simon M.; Johnston, Gordon A.; Moriarty, Andrew S.; Newbronner, Elizabeth; Paterson, Alastair; Spanakis, Panagiotis; Wadman, Ruth; Walker, Lauren; Peckham, Emily (Frontiers in Psychiatry, 2022)
Objectives Sleep problems are a transdiagnostic feature of nearly all psychiatric conditions, and a strong risk factor for initial and recurrent episodes. However, people with severe mental ill health (SMI) are often excluded from general population surveys, and as such the extent and associates of poor sleep in this population are less well understood. This study explores sleep health in an SMI sample during the Covid-19 pandemic, using multiple regression to identify risk factors, including daily routine, wellbeing and demographics. Methods An existing cohort of people with an SMI diagnosis were sampled. Participants were invited to complete a self-report survey about their health and the impacts of Covid-19 and associated public health measures. Sleep duration, efficiency, and quality were measured using items from the Pittsburgh Sleep Quality Index (PSQI). Results 249 adults (aged 21-84 years) completed the survey. Mean sleep duration and efficiency were similar to general population estimates, at 7h 19m and 78%, respectively. However, 43% reported “bad” sleep quality that was associated with being younger in age as well as disturbed routine and declined wellbeing. Indeed, 37% reported a disturbed routine during the pandemic. Conclusions High estimates of perceived poor sleep quality in the SMI population align with previous findings. Supporting people with SMI to maintain routine regularity may work to protect sleep quality and wellbeing. Future research should more closely examine sleep health in people with SMI, using accessible and scalable measures of objective and subjective sleep, examining longitudinal trends.